Early maternal separation enhances melanoma progression in adult female mice by immune mechanisms. Issue 1 (28th June 2021) - Barreto, Francisco Stefânio; Ribeiro, Wesley Lyeverton Correia; Cavalcanti, Bruno Coêlho; Silva, Paulo Goberlânio de Barros; Soares de Sousa, Caren Nádia; Vasconcelos, Germana Silva; Nunes, Ana Paula Negreiros; Moraes Filho, Manoel Odorico de; Macedo, Danielle S.
Abstract: Maternal separation (MS) is a risk factor for major depressive disorder. Both cancer and depression seem to share a common biological link. Here, we evaluated the progression of melanoma and the underlying mechanisms related to this progression, namely cell proliferation and apoptosis, in adult female mice exposed to MS. Female C57BL/6 mice were exposed to MS for 60 min/day during the first 2 postnatal weeks (here called MS mice) or left undisturbed (here called non‐MS mice). Melanoma cells were inoculated subcutaneously into the axillary region of adult animals, and tumor progression was evaluated for 25 days. Adult MS mice presented depressive‐like behavior and working memory deficits. MS accelerated murine melanoma growth by mechanisms related to decreased apoptosis and increased cell proliferation rate, such as increased expression of IL‐6 and mTOR. MS stimulated eukaryotic elongation factor 2 expression and increased the number of circulating monocytes and DNA damage in peripheral blood leukocytes, an effect associated with oxidative DNA damage. In conclusion, MS accelerated the progression of murine melanoma by mechanisms related to tumor proliferation and apoptosis, revealing a relationship between adverse childhood experiences and cancer progression, particularly melanoma. Abstract : Our results revealed that the exposure of female mice to early life stress is a risk factor for melanoma progression, possibly contributing to immune escape. This result opens new avenues for the study of adverse childhood experiences in melanoma growth to guide the development of precision protocols for treating this disease, and more importantly, preventive approaches to minimize this risk. Future studies should evaluate HPA axis dysfunction and β2‐adrenergic receptors to better elucidate the link between early life stress and melanoma progression.